Apollo 13 to the edge and back - Buckner, Noel.; Whittlesey, Rob.; Lyman, Will.; Lovell, Jim.; Aaron, John.; Haise, Fred, 1933-; Kranz, Gene.; WGBH (Television station : Boston, Mass.); Asahi National Broadcasting Company Ltd.; Central Independent Television; WGBH Video (Firm); Tiglon (Firm) ([South Burlington, Vt.] : WGBH Boston Video, 1995)
Presents a factual account of the ill-fated Apollo 13 space mission to the moon. Shows how the ground controllers had to solve the difficult problem of getting the astronauts James Lovell, Fred Haise, and Jack Swigert back to Earth with limited air, water, and electricity. Includes interviews with the astronauts, their families, and the scientists who worked on the mission.
The race to the moon -- "Houston, we have a problem" -- The need for redundant systems -- Help on the ground -- The far side of the moon -- Waiting and enduring -- Correcting the trajectory -- Re-entry.
Originally broadcast on television as an episode of the television program Nova in 1994.
Region 0 (all regions), full screen (1.33:1) presentation; Dolby digital stereo.
Music, Sheldon Mirowitz.
Narrator, Will Lyman.
Interviewees, James Lovell, John Aaron, Fred Haise, Gene Kranz, Jack Swigert, Alexei Leonov, Sy Liebergot, Mary Haise, Barbara Lovell.
MPAA rating: Not rated.
Keywords: Lovell, Jim; Haise, Fred, -- 1933-; Swigert, John L. -- 1931-1982.; Apollo 13 (Spacecraft) -- Accidents; Apollo 13 (Spacecraft); United States. -- National Aeronautics and Space Administration; Space vehicle accidents -- United States; Space flight to the moon; Astronauts -- United States; Documentary -- Feature; Adventure (Nonfiction); Films for the hearing impaired